Enhancing teacher creativity in digitalizing math-literacy modules through technological pedagogical content knowledge training - Jamaan, Elita Zusti; Yerizon, Yerizon (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Mathematical literacy is one of the abilities that must be mastered by teachers. To increase teachers' creative competence, digital modules oriented towards mathematical literacy are supported by Technological Pedagogical and Content Knowledge (TPACK) training. This study aims to evaluate the validity and practicality of digital modules oriented towards mathematical literacy. This study uses the design research method with the Plomp model, which consists of three stages: preliminary research, the prototype stage, and the evaluation stage. The instruments used were validation sheets for material experts and media experts, as well as student and teacher response questionnaires to see the effectiveness and practicality of the digital modules that had been developed. The results of the study show that digital modules oriented towards mathematical literacy using TPACK training have been successfully carried out. Based on the results of the analysis, effectiveness, and practicality, the feasibility of the module is 87.65%, which is in the very good category. Therefore, it can be concluded that the developed mathematical literacy-oriented digital modules have valid, practical, and effective qualities to enhance teacher creativity.